2011
DOI: 10.1074/jbc.m111.225813
|View full text |Cite
|
Sign up to set email alerts
|

T-LAK Cell-originated Protein Kinase (TOPK) Phosphorylation of MKP1 Protein Prevents Solar Ultraviolet Light-induced Inflammation through Inhibition of the p38 Protein Signaling Pathway

Abstract: Solar UV radiation is a major environmental factor that causes DNA damage, inflammation, and even skin cancer. T-LAK cell-originated protein kinase (TOPK) is expressed widely in both normal and cancer cells and functions to inhibit apoptosis and promote carcinogenesis. However, its function in inflammation is not known. The p38 MAPK signaling pathway plays an important role in solar UV light-induced inflammation. In this study, we found that TOPK negatively regulated the activity of p38␣ by phosphorylating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 34 publications
1
38
0
Order By: Relevance
“…It has been suggested that some stimuli including TPA or UVB positively regulate TOPK activity (12,17,19). However, information about signaling pathways or stimuli triggering TOPK activation is still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that some stimuli including TPA or UVB positively regulate TOPK activity (12,17,19). However, information about signaling pathways or stimuli triggering TOPK activation is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate here that TOPK functions as a novel target molecule of doxorubicin, implying a critical role for TOPK in doxorubicin-induced cervical cancer cell death. Some molecules, such as p38 MAPK, JNK, phosphatase MKP1, and peroxiredoxin 1, have been proposed to act as downstream substrates for TOPK (12,(17)(18)(19). However, evidence for downstream targets of TOPK still remains elusive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High TOPK expression can promote cell proliferation [11][12][13] and prevent apoptosis [14,15] and is associated with a poor prognosis [16][17][18][19]. Moreover, TOPK expression may play an important role in the progress of cytokinesis and inflammation [20][21][22]. However, the detailed mechanism of TOPK signaling in lung adenocarcinoma remains unclarified.…”
Section: Introductionmentioning
confidence: 95%
“…22 This would seem to suggest that a hereditary predisposition may be the reason that inflammation was severe in some pterygia. Failure to detect MMP expression in fibroblasts or stroma contradicts a previous report, 7 perhaps due to persistent exposure to sunlight without wearing spectacles which may reduce UV radiation reaching the eyes.…”
mentioning
confidence: 99%